Gaddafi's harem the story of a young woman and the abuses of power in Libya - Cojean, Annick (Grove Press, 2013)
Soraya was just fifteen, a schoolgirl in the coastal town of Sirte, when she was given the honor of presenting a bouquet of flowers to Colonel Gaddafi on a visit he was making to her school the following week. Soon afterwards, she was summoned to Bab al-Azizia, Gaddafi's palatial compound near Tripoli, where she joined a number of young women who were violently abused, raped and degraded by Gaddafi